Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a,6x-3-5x+15+18x-24=24
19x-12=24
19x=36
x=36/19
c,10x-6x2+6x2-10x+21=3
0x=-18
không có x
d,3x2+3x-2x2-4x=-1-x
x2-x=-1-x
x2-x+x=-1
x2=-1
không có x thỏa mãn
1) \(-6x^4+4x^3-2x^2\)
2) \(=x^2+4x-21-x^2-4x+5=-16\)
3) \(=6x^2-4x-x^2-4x-4=5x^2-8x-4\)
4) \(=2x^3-4x^2-8x-3x^2+6x+12=2x^3-7x^2-2x+12\)
b) \(x^2-\left(x+4\right)\left(x+3\right)=24\)
\(\Leftrightarrow x^2-\left(x^2+7x+12\right)=24\)
\(\Leftrightarrow x^2-x^2-7x-12=24\)
\(\Leftrightarrow-7x-12=24\)
\(\Leftrightarrow-7x=36\)
\(\Leftrightarrow x=\frac{-36}{7}\)
a) \(x^2-x\left(2x+3\right)=2x-x^2+1\)
\(\Leftrightarrow x^2-2x^2-3x=2x-x^2+1\)
\(\Leftrightarrow5x+1=0\)
\(\Leftrightarrow x=\frac{-1}{5}\)
x^2 -2x = 24
=> x^2 - 2x - 24=0
=>x^2 -8x+6x - 24 = 0
=> ( x^2- 8x)+( 6x-24) = 0
=> x(x-8) + 6(x-8) = 0
=> (x+6)(x-8)=0
=>\(\orbr{\begin{cases}x=-6\\x=8\end{cases}}\)
a: \(\left(x+1\right)^3+\left(x-2\right)^3=2x^3+2\left(2x-1\right)^2-9\)
\(\Leftrightarrow x^3+3x^2+3x+1+x^3-6x^2+12x-8=2x^3+2\left(4x^2-4x+1\right)-9\)
\(\Leftrightarrow2x^3-3x^2+15x-7=2x^3+8x^2-8x-7\)
\(\Leftrightarrow-11x^2+23x=0\)
\(\Leftrightarrow x\left(-11x+23\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=0\\x=\dfrac{23}{11}\end{matrix}\right.\)
\(\left(2x+3\right)\left(x-2\right)-2x\left(x-3\right)=24\)
\(\Leftrightarrow2x^2-x-6-\left(2x^2-6x\right)=24\)
\(\Leftrightarrow5x=30\)
\(\Leftrightarrow x=6\).